Positive sexuality, relationship satisfaction, and health: a network analysis - Andreoli, Giovanbattista; Rafanelli, Chiara; Gremigni, Paola; Hofmann, Stefan G.; Casu, Giulia (Frontiers in Psychology, 2024)
Positive sexuality, defined as the happiness and fulfilment individuals derive from their sexual experiences, expressions, and behaviors, has been linked to relationship satisfaction and health. However, the intricate associations between positive sexuality and relationship functioning and health indicators have rarely been explored from a network perspective. This approach, by analyzing the interconnections among these factors within a broader system, can offer insights into complex dynamics and identify key variables for targeted interventions. The present study applied network analysis to uncover the interconnections between positive sexuality, relationship satisfaction, and health indicators, highlight the most relevant variables and explore potential gender-based differences in a sample of 992 partnered individuals (51% women, aged 18-71 years). Networks were estimated via Gaussian Graphical Models, and network comparison test was used to compare men and women. Results indicated that variables related to positive sexuality were more highly interconnected than the rest of the network. There were small-to-negligible connections between positive sexuality and relationship satisfaction variables, both of which had negligible or no connections with health. The network was globally invariant across gender, though a few connections were gender-specific. The most important variables, regardless of gender, related to pleasurable feelings during sexual intercourse. The findings underscore the importance of enhancing positive sexual experiences within intimate relationships and have implications for research and clinical practice in positive sexuality.